ELITE CAPTURE IN AGRARIAN REFORM: AN ANALYSIS OF NORMATIVE VULNERABILITY IN INDONESIA - Nurul Adliyah; Rizka Amelia Armin; Mustaming Mustaming; Hamsah Hasan (Datuk Sulaiman Law Review (DaLRev), 2025)
Contestation over land rights involving communities, corporations, and the state indicates that the agrarian reform agenda in Indonesia has not been fully realized. Normatively, agrarian reform is positioned as a corrective measure to address land tenure inequality, while promoting social justice and enhancing the welfare of smallholder farmers. Through the existing schemes, state land and land released from forest areas are intended to be redistributed to priority beneficiaries, particularly small farmers, indigenous peoples, and other vulnerable groups. However, its implementation reveals a tendency toward elite capture, as evidenced by the inclusion of actors possessing superior political, economic, and social power as beneficiaries, which may potentially displace the intended priority groups. This study aims to analyze the normative vulnerabilities within Indonesia’s agrarian reform legal framework that enable such practices. It employs normative legal research using statutory and conceptual approaches. The findings demonstrate that agrarian reform implementation remains dominated by asset legalization oriented toward administrative outputs and has not fully promoted structural transformation in land tenure. The existing regulatory framework contains normative vulnerabilities, reflected in the open-textured formulation of beneficiary criteria, heavy reliance on administrative discretion during verification processes, and weak post-redistribution monitoring mechanisms. These vulnerabilities create a legal opportunity structure for the expansion of patronage and elite capture, which may reproduce land inequality. This article argues that elite capture should not be viewed merely as an implementation failure but as a consequence of a normative design insufficiently insulated from power asymmetries.